Komunikasi Digital dalam Jual Beli Online melalui Sosial Media Instagram - Febri Bayu Andriawan Bayu (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
The purpose of this study is to determine digital communication in online buying and selling through social media Instagram in Pasir Lor Village, Banyumas Regency, Central Java. The approach uses a descriptive qualitative based, involving 20 subjects who have Instagram accounts (both as sellers and buyers). Data were collected and supplemented with interviews and observations when conducting online buying and selling services. The results showed that: digital communication on subjects in Pasir Lor Village by conducting digital interactions between sellers and buyers either through chat, DM or the comment column. The integrity and honesty of the seller in buying and selling online is the main bargaining power for buying and selling online, so that you can get fast response and service from the seller, which can add valuea to online sales through Instagram social media. Digital communication is also supported by the ease of accessing and applying Instagram's social media features so as to provide a positive response for all circles of society.